﻿Analysis of the effects of habitat characteristics, human disturbance and prey on felids presence using long-term community monitoring information - J. Roberto Sosa-López; Nydia Nicté Díaz Bernal; Eugenio Padilla; Miguel Briones-Salas (Nature Conservation, 2023)
Predator species are essential for ecosystems as they maintain the ecological integrity of the habitat. Particularly, felids populations have declined globally due to their sensitivity to habitat disturbances. Nevertheless, in Mexico, there are areas protected by indigenous communities to preserve a portion of their territory, benefiting multiple species, including felids. Although the National Commission of Natural Protected Areas of Mexico sponsors a long-term national-wide communal monitoring programme using camera traps, there is not a systematic analysis of the information generated by the programme. We assessed the occurrence of three felids species known to occur in a Zapotec indigenous community conservation area in Oaxaca, Mexico. Specifically, we evaluated how habitat characteristics, human disturbance and prey influence felids’ occurrence across the protected area. None of the variables explained better than the null model the proportion of sites used by Pumas (Puma concolor). Bobcats and Margays favour areas with medium-sized prey. Our study shows the importance of community-based monitoring and information systems (CBMIS) for identifying communal reserve characteristics that contribute to the occupation of carnivores. Further, our results also suggest that management should consider the habitat requirements of felids´ prey. By understanding wildlife habitat use, communal authorities could improve sustainable forest management within the reserves.